Implementasi Kebijakan Badan Narkotika Nasional (BNN) Dalam Pencegahan Dan Pemberantasan Narkotika Di Kota Tanjungpinang - Hendrayady, Agus; Edison, Edison; Supriyadi, Jepri (Jurnal Ilmu Administrasi Negara (JUAN), 2015)
Implementasi Kebijakan Badan Narkotika Nasional (BNN) DalamPencegahan Dan Pemberantasan Narkotika Di Kota Tanjungpinang Jepri Supriadi Agus HendrayadyEdison (agushendrayady05081973@gmail.com) (Jurusan Ilmu Administrasi Negara FISIP UMRAH) Abstract: The national narcotics agency is one of the associated with narcotics but police and judicial , narcotics is a matter of each region in Indonesia including Tanjungpinang city . Where he financial any number of to always ride, in 2013 that as many as 1 tissue consisting of the 3, then 2014 up to 4 network with of9, in 2015 as per 31 january already 5 tissue arrested by bnnk Tanjungpinang, besides the number involved increase in other side has been a Is the lack of filter facilities for narkotika to the city Tanjungpinang.Through a harbor not facility instrument x-tray in measuring the author of the implementation of olicies based on the theory of Edward III who where there are four points to measure namely communication, source of source Disposition and bureaucratic structure, researchers took analysis technique with descriptive of qualitative methods, In research it consists of three informen namely two people in the field of prevention in the field of eradication one person and one that is, the leader bnnk tanjungpinang key informants After implemented research policy related to the implementation of the national narcotics agency ( bnn ) in the prevention and eradication narcotic in Tanjungpinang city, Going well according to annual work plans and meet the target of policy in the field of prevention and eradication But what was being obstacle on implementing this policy associated on inadequate facilities and human resources. Where bnnk Tanjungpinang not meet minimum number of employees in the agency set by the republic of indonesia One in which at least 70 people set employees but bnnk Tanjungpinang employees only have 29